Medicinal Properties of Rosa canina L. - Amin Selahvarzian; Abuzar Alizadeh; Peyman Amanolahi Baharvand; Omayma A. Eldahshan; Bahram Rasoulian * (Lorestan University of Medical Sciences, 2018)
Dog rose or Rosa canina L. is a perennial shrub that belongs to Rosacea family. It grows wild at the margin of forests, puddles of water, shrubberies and pastures. Rosa canina L. has been used for long years as a source of vitamins, medicinal supplements, and food throughout the world. It contains various vitamins (especially vitamin C) and other valuable compounds such as polyphenols, carotenoids, carbohydrates and fatty acids. The medicinal properties of rose hip in the symptomatic treatment of osteoarthritis, rheumatism and common cold are discussed in this paper. Moreover, there are evidences about anti-bacterial, anti-cancer, anti-diabetic and anti-obesity properties of this medicinal plant that have been reviewed in this article.